Priority of Criteria for Agritourism Development in Bali - Agung Suryawan Wiranatha; I Gusti Ayu Oka Suryawardani; Christine PETR; I Putu Eka Nila Kencana (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
Agritourism in Bali has not been developed optimally yet. As a basis for development of agritourism, the criteria should be determined and priorities among criteria need to be set. The objectives of this research were: (i) to identify criteria for agritourism development; and (ii) to analyze the priorities for selected criteria according to the agritourism stakeholders in Bali. This research implemented Analytic Hierarchy Process (AHP) method which involved 20 key informants representing agritourism stakeholders. The finding was the priority criteria for agritourism development in Bali, namely: (1) Attractions, followed by (2) Local Community Involvement, (3) Ancillary Services, (4) Marketing, (5) Amenities, and (6) Accessibility. This kind of research has not been undertaken previously in Bali. It contributes to academic and practical implications, particularly in agritourism development planning in Bali, in which development of agritourism should be focused on the diversification of agritourism attractions supported by professional management and community participation.